Motor profile of children between 3 and 4 years old attending a community daycare center (Revista Contexto & Saúde, 2023)
Objective: To outline the motor profile of children from three to four years old who attend the community daycare, observing their motor age in the following aspects: fine motor skills, gross motor skills, balance, body schema, spatial organization and temporal organization, as well as, the influence of the environment (space and the furnishings) in their development. Materials and methods: The design of the study was cross-sectional and exploratory. The instruments used were the Scale of Motor Development (EDM) for motor evaluation, and the Infant/Toddler Environment Rating Scale, Revised (ITERS-R) to evaluate the environment in the aspect of “space and furnishings” of the daycare. 14 children participated, seven males and seven females, whose mean age was 3.52 (±0.29) years old. Results: According the mean of general motor age 38.07 (±9.08) months and the mean of chronological age 42.29 (±3.47) months, the participants showing a negative motor age. Most children (71.4%) were developing within normality. Their highest mean score (103±39.78) was in the body scheme dimension (QM4), while the lowest (70±23.52) was in balance (QM3), the latter result being an index for the risk of delayed development. The girls developed better than the boys, with a general motor age of 41.71 (±6.90) and 34.43 (±10) months, respectively. The environment was classified as having the minimum adequate quality, with a score of 3.2 in the ITERS-R. Conclusion: Although the children had a negative general motor age, children presented an adequate motor profile for their age, and the evaluation of the environment of the daycare had no negative influences on their development.
Keywords: Child development; child; child day care centers